Identification by proximity labeling of novel lipidic and proteinaceous potential partners of the dopamine transporter - Piniella, Dolores; Martínez Blanco, Elena; Bartolomé Martín, David; Sanz Martos, Ana B.; Zafra, Francisco (My University, 2021)
Dopamine (DA) transporters (DATs) are regulated by trafficking and modulatory processes that probably rely on stable and transient interactions with neighboring proteins and lipids. Using proximity-dependent biotin identification (BioID), we found novel potential partners for DAT, including several membrane proteins, such as the transmembrane chaperone 4F2hc, the proteolipid M6a and a potential membrane receptor for progesterone (PGRMC2). We also detected two cytoplasmic proteins: a component of the Cullin1-dependent ubiquitination machinery termed F-box/LRR-repeat protein 2 (FBXL2), and the enzyme inositol 5-phosphatase 2 (SHIP2). Immunoprecipitation (IP) and immunofluorescence studies confirmed either a physical association or a close spatial proximity between these proteins and DAT. M6a, SHIP2 and the Cullin1 system were shown to increase DAT activity in coexpression experiments, suggesting a functional role for their association. Deeper analysis revealed that M6a, which is enriched in neuronal protrusions (filopodia or dendritic spines), colocalized with DAT in these structures. In addition, the product of SHIP2 enzymatic activity (phosphatidylinositol 3,4-bisphosphate [PI(3,4)P2]) was tightly associated with DAT, as shown by co-IP and by colocalization of mCherry-DAT with a specific biosensor for this phospholipid. PI(3,4)P2 strongly stimulated transport activity in electrophysiological recordings, and conversely, inhibition of SHIP2 reduced DA uptake in several experimental systems including striatal synaptosomes and the dopaminergic cell line SH-SY5Y. In summary, here we report several potential new partners for DAT and a novel regulatory lipid, which may represent new pharmacological targets for DAT, a pivotal protein in dopaminergic function of the brain.